Pengaruh aktivitas promosi terhadap minat pembelian ulang dengan loyalitas merk sebagai variabel moderasi pada smartphone Samsung di Surabaya - Tedjo, Andrew Gunawan (Kajian Ilmiah Mahasiswa Manajemen, 2015)
The purpose of this research is to identify the impact of promotion activities include: advertising, sales promotion, personal selling, and publicity toward repurchase intention for Samsung smartphone. This research is identify the moderated effect of brand loyalty on the influenced of advertising, sales promotion, personal selling, and publicity toward repurchase intention for Samsung smartphone. The number of samples are: 100 samples. Data analysis technique by moderating regression using SPSS program. The result showing that the promotion activities include: advertising, sales promotion, personal selling, and publicity influence repurchase intention for Samsung smartphone. Brand loyalty is the moderating variable of the relationship among advertising, sales promotion, personal selling, and publicity toward repurchase intention for Samsung smartphone. Brand loyalty is the pure moderating variable, so it is not the independent variable for the relationship of advertising, sales promotion, personal selling, and publicity toward repurchase intention for Samsung smartphone.